GEOLOGICAL MODEL MIDDLE GUMAI SANDSTONE OF WEST JAMBI, SOUTH SUMATRA BASIN - Surtiati, Yatty
In the regional stratigraphy, Gumai sediment was deposited in the Jambi Basin as thick shale deposits around 300 to 400 meters with sandstone intercalations in the deposited middle known as the Middle Gumai. Middle Gumai Reservoir is already proven as a reservoir of gas producers in the Rengan Condong and Muara Bulian study area but until now the direction of the sedimentaion, geometry and reservoir quality is still not known. The objective of this study is to determine the geometry and reservoir quality of Middle Gumai sandstone, and the hypothesis in this study is it is expected that in the Middle Gumai formation there is sandstone deposits that has potential as a reservoir with channel geometry. The results of this study is expected to provide significant contribution for reviewing the potential of the reservoir in the surrounding area being studied. The method used to study the sedimentation pattern in the study area is by reviewing the RMS amplitude attribute map which is then validated against the well data. The well data used is Gamma Ray log using electrofacies approach. The geometry of interpretation result using the geophysics and geologic approach is the channel/lobe geometry. The sedimentation direction in the study area as a result of using the RMS amplitude attribute shows as if it is from the north. The deviation of the sedimentation direction could be due to intrusion, volcanic rock or local highs. Based on the dipmeter data of near well, the area to the north of the study area, it can bee seen that the sedimentation direction is from the north west and this is in line with the regional sedimentation direction. The deviation of the sedimentation direction in the study area is caused by the existence of local highs located at the south east area of the study area. Accoustic impedance map is used to review the reservoir quality, whereby according to the map and validated using petrophysics analysis the reservoir quality of Middle Gumai sandstone laterally has a porosity of medium-good which is about 18 -23.5 %. The results of this study provide exploration opportunities with objective in the Middle Gumai sandstone, especially in southern areas where there is no exploration drilling yet. By analogy of the tectonic conditions, especially the role of Tembesi fault, it is alleged that the Bukit Paku-Batu Ampar and Karang Makmur area has a similar condition.